2011
DOI: 10.1111/j.1447-0756.2010.01466.x
|View full text |Cite
|
Sign up to set email alerts
|

Utility of the pulsatility index of the uterine arteries and human chorionic gonadotropin in a series of cases of placenta accreta

Abstract: The conservative management of retained placenta accreta has been proposed as an alternative option in selected cases. Three patients under conservative management of placenta accreta were followed using the pulsatility index of the uterine arteries and the β fraction of human chorionic gonadotropin to determine the degree of vascularity between the uterus and the placenta. In this series of cases of conservative management of placenta accreta, the pulsatility index of the uterine arteries showed a better corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…The half-life of serum hCG elimination is 5.2–6.1 days during conservative management of retained adherent placenta [ 12 , 13 ]. It is reported that serum hCG level drops to negative 21–35 days after delivery when leaving adherent placenta remnants in situ [ 14 ], though it extends to 10 weeks after delivery in a few cases [ 15 ]. While the half-life of serum β-hCG was 32.3h after normal delivery without placenta remnants.…”
Section: Discussionmentioning
confidence: 99%
“…The half-life of serum hCG elimination is 5.2–6.1 days during conservative management of retained adherent placenta [ 12 , 13 ]. It is reported that serum hCG level drops to negative 21–35 days after delivery when leaving adherent placenta remnants in situ [ 14 ], though it extends to 10 weeks after delivery in a few cases [ 15 ]. While the half-life of serum β-hCG was 32.3h after normal delivery without placenta remnants.…”
Section: Discussionmentioning
confidence: 99%
“…Serum beta-HCG level came down to nonsignificant levels only in 68 and 50 days following delivery (Table 1). Duenas-Garcia et al reported 3 cases where beta-HCG came to <5 IU/L in 21 and 35 days [27]. There is conflicting evidence for serum beta-HCG as a surrogate marker of placental involution [14].…”
Section: Discussionmentioning
confidence: 99%
“…There is conflicting evidence for serum beta-HCG as a surrogate marker of placental involution [14]. Some studies have suggested that decreasing beta-HCG levels do not correlate with placental involution [19,27,28]. Furthermore, undetectable beta-HCG levels do not guarantee complete resorption of retained placental tissue according to previously reported literature [22].…”
Section: Discussionmentioning
confidence: 99%
“…75,76,90) However, such interventions can cause unanticipated massive bleeding or damage to adjacent organs, such as, the bladder or ureters. 18,71,73,91) Moreover, a large retrospective study showed that spontaneous placental resorption was observed in 75% of the cases (87/116) managed by watchful waiting. 33) Indeed, a number of case reports and short case series support this evidence.…”
Section: Postoperative Managementmentioning
confidence: 99%
“…93) Another study also demonstrated spontaneous cessation of placental perfusion 9-13 weeks postoperatively. 9,67) The potential alternative to evaluate a potential risk of hemorrhage may be the pulsatility index of uterine arteries 91,94) and serum human chorionic gonadotropin (hCG). 93) Serum hCG levels were significantly correlated with dynamic MRIbased placental vascular volume, and placental blood flow disappeared on follow-up ultrasonography, almost coincident with a fall in hCG to undetectable levels.…”
Section: Delayed Hemorrhagementioning
confidence: 99%